Antibacterial Analyse of Perovskite - 杨合 刘东 薛向欣 (Shanghai jiao tong da xue xue bao, 2012)
We mainly studied the antibacterial properties of perovskite. Its structure was evaluated by X-ray diffractometer （XRD）, scanning electron microscope （SEM）, and ultraviolet-visible （UV-vis） absorption spec- trometer etc. The antibacterial properties of perovskite to Candida albicans （ATCC10231）, Escherichia coli （ATCC25922） and Staphylococcus aureus （ATCC6538） were investigated by the flask oscillation method. The results show that the perovskite has strong antibacterial ability, and continued antibacterial properties; its steril- ization rates are 87.00%, 99.50%, 96.22% respectively to these three bacteria.